Anatomical Site, Viral Ribonucleic Acid Abundance, and Time of Sampling Correlate With Molecular Detection of Severe Acute Respiratory Syndrome Coronavirus 2 During Infection. (8th December 2021) - Lantry, F Julian; Epsi, Nusrat J; Pollett, Simon D; Simons, Mark P; Lindholm, David A; Colombo, Rhonda E; Fries, Anthony C; Maves, Ryan C; Ganesan, Anuradha; Utz, Gregory C; Lalani, Tahaniyat; Smith, Alfred G; et al.
Abstract: Background: Nasopharyngeal (NP) swabs are the standard for SARS-CoV-2 diagnosis. If less invasive alternatives to NP swabs (eg, oropharyngeal [OP] or nasal swabs [NS]) are comparably sensitive, the use of these techniques may be preferable in terms of comfort, convenience, and safety. Methods: This study compared the detection of SARS-CoV-2 in swab samples collected on the same day among participants with at least one positive PCR test. Results: Overall, 755 participants had at least one set of paired swabs. Concordance between NP and other swab types was 75% (NS), 72% (OP), 54% (rectal swabs [RS]), and 78% (NS/OP combined). Kappa values were moderate for the NS, OP, and NS/OP comparisons (0.50, 0.45, and 0.54, respectively). Highest sensitivity relative to NP (0.87) was observed with a combination of NS/OP tests (positive if either NS or OP was positive). Sensitivity of the non-NP swab types was highest in the first week postsymptom onset and decreased thereafter. Similarly, virus RNA quantity was highest in the NP swabs as compared with NS, OP, and RS within two weeks postsymptom onset. OP and NS performance decreased as virus RNA quantity decreased. No differences were noted between NS specimens collected at home or in clinic. Conclusions: NP swabs detected more SARS-CoV-2 cases than non-NP swabs, and the sensitivity of the non-NP swabs decreased with time postsymptom onset. While other swabs may be simpler to collect, NP swabs present the best chance of detecting SARS-CoV-2 RNA, which is essential for clinical care as well as genomic surveillance. Abstract : Nasopharyngeal swabs performed better in the detection of SARS-CoV-2 than other same-day collected swab types (oropharyngeal, anterior nasal, rectal). Timing of sample collection relative to symptom onset and virus ribonucleic acid quantity, but not self-collection, were associated with SARS-CoV-2 detection